Pedagogical Press Ukrainian Diaspora Studies as a Source of Educational Thought and Ukrainian Foreign National Education - Ivan Rusnak; Ganna Bygar; Svitlana Romanyuk (Pedagogical Discourse, 2013)
Publications of Ukrainian Canadian educational press (magazines «Teacher's word», «Ridna Shkola», «Life and School», «Theme», «Ridnoshkilnyk», «Ukrainian teacher in Canada», «Vidhuknitsya») devoted to various problems of development of native language schooling of Ukrainians in the diaspora in the second half of XX – beginning of XXI century, as a source of the research of its history, are analysed. reveals Its role in covering organizational and didactic principles of native Ukrainian schools and courses, in scientific and methodological support of educational process and in the formation of human resources for the system of Ukrainian education in Canada is revealed. It is stated that publications of the Canadian Ukrainians in  ethnic educational press is not only a powerful  base for scientific research, but also can be successfully used in the educational process of  higher educational pedagogical institutions of different levels of accreditation and postgraduate pedagogical education.